Health Education on Hand, Foot, and Mouth Disease (HFMD) and Training on Proper Handwashing with Soap (CTPS) for Parents of Toddlers at South Denpasar I Primary Health Center - Brata Wiguna I Komang; Maha Dananjaya Nyoman; Surya Andreastika I Putu; Ni Wayan Widhidewi (Mattawang: Jurnal Pengabdian Masyarakat, 2026)
The UPTD South Denpasar I Primary Health Center is facing a high incidence of Hand, Foot, and Mouth Disease (HFMD) among toddlers, accompanied by a low level of adherence to the six-step handwashing with soap (CTPS). Limited knowledge regarding HFMD transmission and insufficient skills in performing proper handwashing increase the risk of disease spread. Maintaining hand hygiene is one of the most effective measures to prevent contact-based infectious diseases; however, its implementation in the community remains suboptimal. This community service program (PKM) proposes a solution through integrated education and training for 17 parents of toddlers, implemented through two main activities: educational sessions on HFMD and hands-on training in the six-step WHO handwashing technique. Program evaluation was conducted using pre-test and post-test assessments. The activities were carried out collaboratively with health workers from the primary health center to ensure program sustainability. The results of the community service showed an average increase in participant`s knowledge of 78.75%. This program is expected to reduce the transmission of HFMD among toddlers and contribute to the achievement of the Sustainable Development Goals (SDGs), particularly Goal 3.